O clima escolar e o som do recreio: entre escutas, observações e relatos - Mariana de Assis Soares (2018)
This dissertation, in the field of sociology of education, aims to investigate possible connections between the school climate and the soundscape of the recess in two elementary schools in the city of Belo Horizonte/MG. Contemplating the plethora of factors previously mentioned by the literature as components of the climate of a school, the sounds of recess are not considered as one of them. In this work, it is proposed that the soundscape of recess should be included as one of these factors, since, even though school noise is easily recognizable, each school has its sound peculiarities, which, theoretically, may result from elements that characterize the environment of the school and influence the perception of this environment. The field research involved seven months of observations in recesses and classrooms in both schools, material collection, and interviews with school staff and students of both institutions. The data collected was analyzed in the light of references in the field of sociology of education and music about school environment and soundscape; some studies about school recess and childrens culture were also considered. Said analysis revealed differences and similarities between the schools regarding their organization, structure, rules, values, and how interpersonal relations take place allowing an analysis and description of the characteristics of the school climate of both schools. Based on the comparison of one institution to the other, it was possible to notice, in the school in which the recess was less noisy, a better disciplinary control and a smaller space for children's culture; and in the school in which the recess was restless and noisier, a more open environment, with more negotiation and more space for the aforementioned culture. Thus, confirming the hypothesis that the sound of recess may be related to the school climate, which can be deepened in following works on other types of school.